2019
DOI: 10.26508/lsa.201800045
|View full text |Cite
|
Sign up to set email alerts
|

d-amino acid oxidase promotes cellular senescence via the production of reactive oxygen species

Abstract: This study reveals a novel role of d-amino acid oxidase in promoting cellular senescence induced by genotoxic stresses via enzymatic generation of reactive oxygen species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The cells were treated with etoposide (Sigma Aldrich, St Louis, MO) or bleomycin (Wako) to induce DNA double-strand breaks. For senescence induction, U2OS and Hs68 cells were treated with 2- and 0.5-μM etoposide, respectively, or 2-μM bleomycin for 48 h and cultured in the medium without the drugs for additional 5 days to develop senescent phenotypes ( 6 , 7 , 8 , 37 ). Transfection with expression vectors was carried out using Effectene Transfection Reagent (Qiagen, Venlo, Netherlands) according to the manufacturer’s instruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were treated with etoposide (Sigma Aldrich, St Louis, MO) or bleomycin (Wako) to induce DNA double-strand breaks. For senescence induction, U2OS and Hs68 cells were treated with 2- and 0.5-μM etoposide, respectively, or 2-μM bleomycin for 48 h and cultured in the medium without the drugs for additional 5 days to develop senescent phenotypes ( 6 , 7 , 8 , 37 ). Transfection with expression vectors was carried out using Effectene Transfection Reagent (Qiagen, Venlo, Netherlands) according to the manufacturer’s instruction.…”
Section: Methodsmentioning
confidence: 99%
“…Although LY6D is often used as a surface marker for leukocyte subset identification because of its lineage-specific expression, the physiological function of LY6D is poorly understood. We have recently identified LY6D to be upregulated specifically in senescent cells by comparing the transcriptome between senescent and apoptotic cells and shown that the upregulation of LY6D is dependent on p53, a crucial transcription factor for the initiation and maintenance of senescence ( 6 , 7 , 8 ). However, it is still unknown whether LY6D functionally contributes to the senescence process because our previous study has shown that ectopic expression of LY6D in osteosarcoma U2OS cells had little effect on senescence induction as determined by colony-forming assay and by senescence-associated β-galactosidase (SA-β-Gal) staining, an established marker of senescence.…”
mentioning
confidence: 99%
“…The major source of ROS originates from mitochondrial production [3], mainly due to complexes I and III function in the respiratory chain [4][5][6]. However, other non-mitochondrial enzymes and protein complexes also produce ROS: among these are nicotinamide adenine dinucleotide phosphate oxidase (NOX) and nitric oxide synthases (NOSs) [7], xanthine oxidase [8,9], the α-ketoglutarate dehydrogenase complex [10,11], including dihydrolipoamide dehydrogenase [12][13][14][15], and d-amino acid oxidases [16][17][18]. Nitric oxide (NO), for instance, produced from sources such as endothelial NOS, contributes to vascular homeostasis, whereas under conditions of oxidative stress such as inflammation, NO interaction with other ROS potentiates cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that ROS accumulation induces DNA damage, resulting in cell cycle arrest. Cellular senescence is a permanent cell cycle arrest induced by stress, including oxidative stress and DNA damage [32,33]. Other studies showed that premature cellular senescence caused by oxidative stress in DP compromised the interaction between the epithelium and DP cells, and the above phenomenon was observed mainly in androgenetic alopecia patients [34,35].…”
Section: Discussionmentioning
confidence: 99%